2020
DOI: 10.1002/aenm.202003203
|View full text |Cite
|
Sign up to set email alerts
|

Co2+/3+/4+‐Regulated Electron State of Mn‐O for Superb Aqueous Zinc‐Manganese Oxide Batteries

Abstract: Aqueous rechargeable Zn–MnOx batteries are very attractive due to their low‐cost and high energy density. However, Mn(III) disproportionation and Jahn–Teller distortion can induce Mn(II) dissolution and irreversible phase changes, greatly deteriorating the cycling life. Herein, a multi‐valence cobalt‐doped Mn3O4 (Co‐Mn3O4) with high capacity and reversibility, which lies in the multiple roles of the various states of doped cobalt, is reported. The Co2+ doping between the phase change product δ‐MnO2 layer acts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
123
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(128 citation statements)
references
References 57 publications
5
123
0
Order By: Relevance
“…There is no peaks of Zn 2p in the pristine NVO (Fig. 5 h), while two peaks corresponding to Zn 2p 1/2 (1045.6 eV) and Zn 2p 3/2 (1022.5 eV) appear in the fully discharged state, indicating the intercalation of zinc ions [ 81 ]. The Zn 2p signals in the fully charged state are also detected, which is consistent with the results of ex situ TEM.…”
Section: Resultsmentioning
confidence: 99%
“…There is no peaks of Zn 2p in the pristine NVO (Fig. 5 h), while two peaks corresponding to Zn 2p 1/2 (1045.6 eV) and Zn 2p 3/2 (1022.5 eV) appear in the fully discharged state, indicating the intercalation of zinc ions [ 81 ]. The Zn 2p signals in the fully charged state are also detected, which is consistent with the results of ex situ TEM.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Chao et al reported that the NiS@ Ni 0.95 Zn 0.05 (OH) 2 used in NZBs has a long life and fast energy response (18.82 kW kg −1 , peak power output of 30 s) [30]. Ionic doping could promote the transmission of ions/electrons and show more redox reactions, thereby contributing to electrochemical performance [31]. Surface modification with the introduction of defects and higher conductivity additives, the surface reactivity and reaction kinetics of electrode materials are improved [32].…”
Section: Introductionmentioning
confidence: 99%
“…[23] Although significant achievements have been made, low capacity for Mnbased and low operating voltages (0.6-0.8 V) for V-based materials still are key bottlenecks for energy density enhancement. [24,25] It charging and enable high operating voltage (≈1.35 V). [26,27] Inspired by this, we, herein, propose to use MnV 2 O 6 (MVO) as a cathode material for high-energy density AZIBs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 23 ] Although significant achievements have been made, low capacity for Mn‐based and low operating voltages (0.6–0.8 V) for V‐based materials still are key bottlenecks for energy density enhancement. [ 24,25 ]…”
Section: Introductionmentioning
confidence: 99%